Guide to the literature for the industrial microbiologist - Hahn, Peter A. (New York : IFI/Plenum, 1973)
Arranged in four sections to give a guide to the literature from 1960-1973. Section one lists 98 textbooks and their tables of contents. Arranged alphabetically by title. Section two provides subject access to articles from ten review publications. Thirty of the major journals are listed. The last section lists several national and international meetings plus some courses.Published 1973
Keywords: Industrial microbiology -- Bibliography